THE INFLUENCE OF THE ASPECTS OF CULTURE, PERSONALITY, AND PUBLIC-PRIVATE RELATIONSHIP ON CORRUPTION IN INDONESIA - Ari Nur Rahman; Mustika Prabaningrum Kusumawati (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
The history of corruption in Indonesia is marked by reforms in handling corruption cases. However, these reforms will not succeed if the culture that drives corruption is still maintained. A low level of trust can increase corruption, because it does not encourage good cooperation between the community and the government.Geographical and historical aspects correlate with the level of corruption. Therefore, certain former colonies also correlate with the level of corruption. Personality is a character owned by a person and is integrated in a unique unit, so that the person can modify and determine the adjustment. This can be seen from the high number of officials in developed countries who resigned after being suspected of being involved in corruption cases.Corruption reduces the performance of institutions in the democratic order, suppresses economic growth, exacerbates the income gap, and causes government instability. Therefore, aspects of culture, personality, and public-private relationship are directly proportional to the occurrence of corruption in Indonesia.